A Brief Moment in the Great Postcolonial Story: Crime, Violence and Grief in Contemporary South African Theatre - Peimer, David (My University, 2022)
Much has been written about Protest Theatre during the apartheid era; and much has been written about the Truth and Reconciliation Commission after the 1994 democratic elections in South Africa. Much has also been written about the profound importance of postcolonial theory in relation to South African, and other African, theatre practices and traditions. This article aims to contribute to the growing knowledge of in-depth and nuanced insights gained from this legacy in the context of current, post-apartheid theatre. This article specifically argues that, in post-apartheid theatre, when the characters and/or audience, collectively experience grief, the traumatic legacy of the binary arrangement of identities (of ‘primitive/civilized, superior/inferior, master/servant’) constructed by and for power during the pre-revolution era, breaks down and the crimes of colonization and apartheid are perceived by the audience. This is seen as a necessary part of the process in the ongoing countering of the received master narrative inculcated by the colonial and apartheid periods. Agreeing with Ash Amin, the paper argues that through such theatre the periphery is liberated and, on those terms, engages with the centre, or historical, hegemonic narrative. From that perspective, history and the present can be grasped and new post-apartheid identities seen as multi-dimensional, non-stereotyped, and in ‘constant production’ are revealed. Applying this notion, one observes that multiple stories emerge to articulate this countering process. But, core to this process, is the subjective and collective experience of grief leading to the binaries collapsing and the crime of the colonial and apartheid project being seen at the core of the traumatic history which informs the contemporary, multi-layered South African experience. The article explores five contemporary South African plays: Bush Tale, Relativity; Township Stories, Hallelujah!, Reach, Armed Response. Notions of postcolonial and identity theory are incorporated in the article as they help illuminate the plays. In addition, insights gained from the Kleinian School of Object Relations psychoanalytic theory help inform notions of how the processes of grief and trauma deepen our understanding of the plays, and the contemporary South African narrative.
Keywords: Drama; Theatre and Performance Studies; postcolonialism